INFLUENCE OF LEADERSHIP, HAPPINESS, INTERPERSONAL COMMUNICATION TO NORMATIVE COMMITMENT OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS IN KAMPAR REGENCY OF RIAU PROVINCE - Sispurwanto, Yedi; Luddin, Muchlis R.; Fitri, Rugaiyah (Journal of Education Research in Administration and Management (JERAM), 2018)
The purpose of this study is to study the influence of leadership, happiness, interpersonal communication to normative commitment of public Junior High School teachers in Kampar Regency of Riau Province. This research uses a quantitative approach with the survey method. The sample of this research is 148 lecturers of civil servant status (PNS) at public Junior High Schools (SMP Negeri) located in Kampar Regency, which is collected from 4 schools, selected based on schools that get the highest National Examination (UN) and National Examination Integrity Index (IIUN) value at 4 sub-districts. The results of this study indicate that (1) leadership has a direct effect on the teacher's normative commitment, (2) happiness directly affects teacher's normative commitment, (3) interpersonal communication has a direct effect on teachers' normative commitment; (4) direct influence toward teacher interpersonal communication (5) happiness directly affects teacher's interpersonal communication, (6) leadership has a direct effect on teacher's happiness, so teacher's normative commitment can be improved if there is a good leadership behavior, happiness in workplace and intimacy in interpersonal communication. Especially for Kampar Regency of Riau Province, the region which is nicknamed “Riau Province' Veranda of Mecca”, to increase teachers' normative commitment is to facilitate the needs related to facilities and infrastructure, programs, activities that can improve science and practice values ​​to muslim teachers because based on the questionnaire results, the majority of teachers responded to the point that: "I pursue the teaching profession as worship to Allah Subhanahu Wata'ala", with a total score of 707. The statements of the teachers are in line with the Vision of RPJPD (Regional Long Term Development Plan) of Kampar Regency Year 2005-2025, namely: "Kampar Regency a County of Culture, Empowerment, within the Religious Society in the year of 2025", and explained to the explanation of the meaning contained in the vision, in point three, : "All components of Kampar regency are determined to make the religious society, where all aspects of life that are run are always based on religious values, in accordance with Kampar community motto to create Kampar district as “Riau Province' Veranda of Mecca”. Keywords: leadership, happiness, interpersonal communication, normative commitment